Qualitative longitudinal assessment of normal occlusion maturation: 40 years of follow-up - Miranda, Felicia (2017)
Introduction: The aim of this study was to evaluate the qualitative occlusal changes in individuals with normal occlusion after a 47 years period follow-up. Material and Methods: An initial sample of 82 White-Brazilian subjects with normal occlusion and dental models performed at 13 years of age was recalled at 60 years of age. Twentyseven individuals were reevaluated at T2. The exclusion criteria were history of orthodontic treatment and complete or extensive tooth loss. The final sample comprised 20 dental models at 13.2 years of age (T1) and 60.9 years of age (T2). Objective Grading System (OGS) and the Six Keys to Normal Occlusion were evaluated in T1 and T2. Subjects also answered a questionnaire on esthetical and occlusion self-perception at T2. Inter-phase comparisons were performed using paired t tests and McNemar test (p<0.05). Descriptive statistics (frequencies) were used for reporting the questionnaire answers. Results: The OGS analysis showed an improvement in the marginal ridge leveling and buccolingual tooth inclination. There was a significant impairment of the anteroposterior occlusal relationship from T1 to T2 with some subjects demonstrating a slight Class III relationship at T2. The six keys to normal occlusal analysis showed a deterioration of the second molars buccolingual inclination, an increase of mandibular incisor crowding and an improvement of second molar mesiodistal angulation. All patients were satisfied with their smiles, with a median grade of satisfaction of 8. Sixty percent of patients had no complaints about their smiles and occlusion. Crowding was the main change noticed from adolescence to sixties and cause a disturbance in 35% of the sample. Conclusion: The aging process impairs some occlusal features of individuals with normal occlusion. However, most of individuals with normal occlusion were satisfied with their esthetics and occlusal comfort at the sixth decade of life.